Peningkatan Self Awareness Anak Usia Dini Melalui Media Video Mitigasi Bencana Gunung Meletus - Ningtyas, Dhita Paranita; Risina, Duana Fera (Al-Athfal: Jurnal Pendidikan Anak, 2018)
This study aims to improve children's self-awareness in disaster response, especially volcanic eruptions with result that children are able to understand the danger of volcanic eruptions since early and have an awareness through a disaster. The subjects were children in group B TK Pertiwi 1 and 2 Samiran, aged 5-6 years. The study was carried out in the village of Samiran because it was an area under the foot of Mount Merapi and Merbabu. This study uses "Action Research" with 2 implementation cycles. This uses Kemmis and MC Taggart procedure which consist of four components, includes: a) planning, b) acting, c) observing, d) reflecting The results are expected that eruption of mountain disaster mitigation videos can improve self-awareness in disaster response so that children have the provision to save themselves and preserve the environment so that the small number of victims because the understanding of disaster mitigation has been obtained since childhood early.